PENGARUH PENDEKATAN KONTEKSTUAL DALAM KURIKULUM MERDEKA TERHADAP PEMAHAMAN KONSEP IPAS PADA SISWA KELAS V SDN 67 RABANTALA KOTA BIMA - Fauzul Qabir; Suriya Ningsyih; Rakhmatul Ummah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was conducted to address the low conceptual understanding of fifth grade students in IPAS subject at SDN 67 Rabantala, Kota Bima. The purpose of the study was to determine the effect of contextual teaching and learning (CTL) approach in the Merdeka Curriculum on students’ conceptual understanding. The method used was a quasi-experimental research with a one group pretest-posttest design. The research subjects were 23 fifth grade students selected through saturated sampling. The research instrument consisted of a multiple-choice test with 15 items that had been tested for validity and reliability, and an observation sheet for the implementation of CTL. Data were collected through pretest and posttest, then analyzed using descriptive statistics, normality test, and paired sample t-test with the help of SPSS 24. The results showed an increase in the average score from 58.26 in the pretest to 83.04 in the posttest. The number of students achieving the Minimum Mastery Criteria (KKM) increased from 30% to 91%. The results of the paired sample t-test obtained a significance value of 0.000 < 0.05, which means that there was a significant difference in students’ conceptual understanding before and after the application of CTL. Thus, CTL is proven to be effective in improving students’ conceptual understanding in IPAS learning.